2+bx=b-3

Simple and best practice solution for 2+bx=b-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2+bx=b-3 equation:


Simplifying
2 + bx = b + -3

Reorder the terms:
2 + bx = -3 + b

Solving
2 + bx = -3 + b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-1b' to each side of the equation.
2 + -1b + bx = -3 + b + -1b

Combine like terms: b + -1b = 0
2 + -1b + bx = -3 + 0
2 + -1b + bx = -3

Add '-2' to each side of the equation.
2 + -1b + -2 + bx = -3 + -2

Reorder the terms:
2 + -2 + -1b + bx = -3 + -2

Combine like terms: 2 + -2 = 0
0 + -1b + bx = -3 + -2
-1b + bx = -3 + -2

Combine like terms: -3 + -2 = -5
-1b + bx = -5

Reorder the terms:
5 + -1b + bx = -5 + 5

Combine like terms: -5 + 5 = 0
5 + -1b + bx = 0

The solution to this equation could not be determined.

See similar equations:

| (2x+5)/(-25)=-2.5 | | f(-3)=3(-3)+4 | | 14.5=-2.4b | | 0.7x=0.7+0.8x | | -48+x=41 | | 13sin(2x)-3=3 | | (2x+250)(2x)=0 | | 3a+20=-2a+40 | | 1+y-6y=y-8y+17 | | 4x^2+500x=0 | | -20=2y+2 | | 4e^6x-16e^3x-9=0 | | -7w-6=-4(w-3) | | 9(w-2)=7w-38 | | 9v+32=5(v+8) | | 4(y-9)=-9y-49 | | 3-3*6-3=x | | -6u+18=-3(u+1) | | y^2(y+5)-16(y+5)=0 | | 2y+3y=-15 | | -9x+19x=220 | | 3-3*2+1= | | 4x+2=-12+50 | | 3m-15-5n+mn=0 | | V=BQU | | 1x+1x+10+40=180 | | 90x-15=15(6c) | | 3x-7(4+2)=-x+2 | | 3(4x+1)-2(3x-4)=1 | | p+18=36 | | 3(4h+6)+2(-6h+9)=(h+2) | | x=-3.5+-0.5y |

Equations solver categories